PENGARUH KEMAMPUAN TEKNIK PERSONAL DAN PARTISIPASI PEMAKAI SISTEM INFORMASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) HULU SUNGAI TENGAH - Rakhmi Ridhawati; Novianti Novianti (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to empirically proved the influence of personal technical skills and participation of users of information systems on the performance of accounting information systems at the regional water company (PDAM) Hulu Sungai Tengah. The population in this study were all employees of the Regional Water Company (PDAM) Hulu Sungai Tengah totaling 60 people. The sampling technique carried out in this study used the Purposive Sampling Technique, with the sample criteria being active employees and willing to be respondents at the Hulu Sungai Tengah Regional Drinking Water Company (PDAM) totaling 50 people. The research method used is a quantitative method. The results of the study showing that the ability of personal techniques and the participation of users of information systems affect the performance of the accounting information system at the Hulu Sungai Tengah Regional Water Company (PDAM), either partially or simultaneously.